Creating and restoring wetlands from theory to practice - Craft, Christopher B. (Elsevier, 2016)
Creating and Restoring Wetlands: From Theory to Practice describes the challenges and opportunities relating to the restoration of freshwater and estuarine wetlands in natural, agricultural, and urban environments in the coming century. The underpinnings of restoration, driven by ecological (disturbance, dispersal, succession) theory, are described and applied to various activities (restoring hydrology, soils, and biota) that are used to improve the short- and long-term success of wetland restoration projects. Unforeseen problems that hinder restoration efforts and solutions to these problems are discussed in this comprehensive book that contains five sections and 13 chapters that include an introduction describing the defining characteristics of wetland – hydrology, soils, biota, the role of theory in guiding wetland succession, ecosystem development following restoration, and differentiating wetland reclamation, restoration, and creation, restoration of various estuarine and freshwater wetlands, case studies of estuarine and freshwater restoration and large-scale restoration, and finally, the future of wetland restoration.--Provided by publisher.